Simultaneous Observations of Electromagnetic Ion Cyclotron (EMIC) Waves and Pitch Angle Scattering During a Van Allen Probes Conjunction. Issue 4 (18th April 2020) - Sigsbee, K.; Kletzing, C. A.; Faden, J. B.; Jaynes, A. N.; Reeves, G. D.; Jahn, J.‐M.
Abstract: On 22 December 2015, the two Van Allen Probes observed two sets of electromagnetic ion cyclotron (EMIC) wave bursts during a close conjunction when both Probe A and Probe B were separated by 0.57 to 0.68  R E . The EMIC waves occurred during an active period in the recovery phase of a coronal mass ejection‐driven geomagnetic storm. Both spacecraft observed EMIC wave bursts that had similar spatial structure within a 1–2 min time delay. The EMIC waves occurred outside the plasmasphere, within Δ L  ≈ 1–2 of the plasmapause and within a few degrees in magnetic latitude of the equatorial plane. The spatial structure of the EMIC wave bursts may have been related to the proton drift paths outside the plasmasphere and influenced by total magnetic field strength variations associated with solar wind pressure enhancements. The EMIC waves were observed in a narrow L shell region from L  ≈ 4.55–5.32 between 10 and 11 magnetic local time (MLT) on the outbound halves of the spacecraft orbits and from L  ≈ 4.82–5.51 between 13 and 14 MLT on the inbound halves of the spacecraft orbits. However, Pc1 pulsations were observed on the ground over a broad range of local times. The anisotropy of the proton pitch angle distributions was enhanced when the EMIC waves were observed. Although the overall radiation belt response during this storm was dominated by acceleration and transport processes, the EMIC waves produced local pitch angle scattering of 13–15 keV protons and 2.1–2.6 MeV electrons, consistent with calculations of the expected resonant energies. Plain Language Summary: In 1958, James Van Allen discovered Earth was surrounded by rings of electrons and ions, now called the radiation belts. In 2012, NASA launched the twin Van Allen Probes to study the radiation belts. Radiation belt electrons traveling near the speed of light can damage communication and weather satellites and pose a risk to astronauts. Electromagnetic waves from 1–2 cycles every 10 min up to radio frequencies (several thousand cycles per second) are critical to radiation belt physics. Some waves energize the radiation belts, while others decrease their strength. We studied electromagnetic ion cyclotron (EMIC) waves (1–4 cycles per second) during a geomagnetic storm. The Van Allen Probes encountered two EMIC wave activity regions 25, 000 km above Earth's surface, one just before local noon and one slightly after local noon. The two satellites were close together and observed the waves in each region simultaneously. The wave activity regions were 2, 000–4, 000 km wide and 8, 000 km across (twice the distance from Washington, DC, to San Francisco). Although this geomagnetic storm increased the global radiation belt strength, EMIC waves ejected electrons and protons from their paths around Earth, temporarily reducing the local radiation belt strength measured by the Van Allen Probes. Key Points: Electromagnetic ion cyclotron waves generated by enhanced solar wind dynamic pressure were observed during the recovery phase of a storm Both of the Van Allen Probes observed electromagnetic ion cyclotron waves with similar spatial structure outside the dayside plasmapause Electromagnetic ion cyclotron waves with amplitudes up to 9 nT produced pitch angle scattering of >10 keV protons and ~2 MeV electrons